2021
DOI: 10.1088/1361-6382/abfed7
|View full text |Cite
|
Sign up to set email alerts
|

Classical and quantum exact solutions for a FRW in chiral like cosmology

Abstract: In this work, first, we study a flat Friedmann–Robertson–Walker Universe with two scalar fields but only one potential term, which can be thought as a simple quintessence plus a K-essence model. Employing the Hamiltonian formalism we are able to obtain the classical and quantum solutions. The second model studied, is also a flat Friedmann–Robertson–Walker Universe with two scalar fields, with the difference that the two potentials are considered as well as the standard kinetic energy and the mixed term (chiral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 86 publications
4
8
1
Order By: Relevance
“…Also, the evolution of |Ψ| 2 is shown for different values of the factor ordering parameter Q; and actually, in all panels the probability density dies away as V and φ 2 evolve. An expected outcome already reported in [39,46,50,59,60]. Moreover, when Q 0 then |Ψ| 2 tends to behave similar to the isotropic case [46].…”
Section: Quantum Schemesupporting
confidence: 69%
See 1 more Smart Citation
“…Also, the evolution of |Ψ| 2 is shown for different values of the factor ordering parameter Q; and actually, in all panels the probability density dies away as V and φ 2 evolve. An expected outcome already reported in [39,46,50,59,60]. Moreover, when Q 0 then |Ψ| 2 tends to behave similar to the isotropic case [46].…”
Section: Quantum Schemesupporting
confidence: 69%
“…On the other hand, the multi-field cosmology paradigm has proven to be an effective framework to account (in a single model) for several important characteristics/ingredients of the universe, e.g., early acceleration (inflation) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], dark matter [26][27][28], late acceleration [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. With respect to early and late acceleration, the crossing of the phantom divide line is a most wanted feature in scalar field cosmology; it has been shown that this crossing cannot be achieved by considering a single scalar field/fluid (unless stability is not demanded) [44].…”
Section: Introductionmentioning
confidence: 99%
“…Before addressing the effective scheme of LQC, we obtain purely classical exact solutions but using the connection triad variables defined by ( 13) and (14).…”
Section: Classical Solutions In Connection Variablesmentioning
confidence: 99%
“…The above remarks provide sufficient motivation for considering the quantum counterpart of classical theoretical frameworks of the Universe which involve non-canonical fields, with a focus on describing (at an effective level) its very early stages of evolution. In this respect, recently, the standard canonical (Wheeler-DeWitt) quantization of some particular chiral cosmology models has been undertaken (in particular, the flat FLRW (see, e.g., [6,13,14]) and Bianchi type I (see, e.g., [15,16]) backgrounds have been thoroughly studied).…”
Section: Introductionmentioning
confidence: 99%
“…Multiscalar field models have been proposed as alternative models for the description of the whole cosmological history [22,23]. In the multiscalar field model the additional degrees of freedom provide new dynamical behaviours in the cosmological dynamics [24][25][26][27][28][29][30]. Some anisotropic exact solutions in multifield cosmology can be found in [20,31,32].…”
Section: Introductionmentioning
confidence: 99%